Education and Training on Feeding Babies and Children from Local Ingredients: Edukasi dan Pelatihan Pemberian Makan Bayi dan Anak dari Bahan Lokal - Evy Kasanova; Lidia Widia; Meyska Widyandini (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Nutritional problems that have the potential to arise include the incidence of malnutrition in infants and toddlers, conditions in which babies do not get breast milk (ASI) due to separation from their mothers, and limitations in the provision of adequate complementary foods (MP-ASI) for toddlers. Good knowledge and skills of mothers in feeding practices can support growth and development and improvement of nutrition in children. This community service activity was carried out in Palingkau Lama Village, Kapuas Regency, Kalimantan Tengah Province. This community service aims to improve the knowledge and skills of pregnant women and mothers of toddlers in the practice of child feeding. Increasing maternal knowledge is carried out through education about PMBA and improving maternal skills is carried out through complementary food preparation training activities, mainly the introduction of the right food texture according to the child's age. The method used consists of the preparation, implementation, and evaluation stages of activities. The results obtained resulted in an increase in maternal knowledge about feeding babies and children using local ingredients.